1975
DOI: 10.1139/f75-268
|View full text |Cite
|
Sign up to set email alerts
|

Minimal Dissolved Oxygen Requirements of Aquatic Life with Emphasis on Canadian Species: a Review

Abstract: This article reviews the sensitivity, responses, response thresholds, and minimum oxygen requirements of marine and freshwater organisms with strong emphasis on Canadian species. The analysis attempts to define low dissolved oxygen thresholds which produce some physiological, behavioral, or other response in different species.Oxygen availability is discussed with reference to seasonal, geographical, or spatial variation in dissolved oxygen. Factors affecting availability of dissolved oxygen include atmospheric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
331
0
4

Year Published

1997
1997
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 481 publications
(348 citation statements)
references
References 0 publications
13
331
0
4
Order By: Relevance
“…Similar to what we observed, elevated turbidity and Chl-a concentrations are often recorded in conjunction with low water levels Boavida 2005, 2007), particularly in nearby reservoirs (Olds et al 2011). Despite a significant difference in dissolved oxygen concentration between pre-drawdown and post-drawdown periods, postdrawdown dissolved oxygen levels were still well above minimal requirements for all fishes in Red Willow (Davis 1975). Neither mean water temperature nor spring warming rate changed, even though the reservoir volume decreased 76%.…”
Section: Water Qualitysupporting
confidence: 82%
“…Similar to what we observed, elevated turbidity and Chl-a concentrations are often recorded in conjunction with low water levels Boavida 2005, 2007), particularly in nearby reservoirs (Olds et al 2011). Despite a significant difference in dissolved oxygen concentration between pre-drawdown and post-drawdown periods, postdrawdown dissolved oxygen levels were still well above minimal requirements for all fishes in Red Willow (Davis 1975). Neither mean water temperature nor spring warming rate changed, even though the reservoir volume decreased 76%.…”
Section: Water Qualitysupporting
confidence: 82%
“…Doudoroff & Shumway (1970), Davis (1975), and the USEPA (1986) summarised studies on lethal concentrations of dissolved oxygen for many species, including salmonids, which are generally considered to be the most sensitive group of freshwater fish.…”
Section: Discussionmentioning
confidence: 99%
“…However, the USEPA (1986) noted that the variability in test conditions used by investigators has made interpretation and generalisation of the scientific data difficult. Furthermore, the rainbow trout used in our experiments were only a few months old and therefore likely to be more sensitive (USEPA 1986) than those used in other experiments (as described in Davis (1975)). Doudoroff & Shumway (1970) reported that for salmonids, mortality or loss of equilibrium usually occurred at concentrations of between 1 and 3 mg litre" 1 , which agrees with our results.…”
Section: Discussionmentioning
confidence: 99%
“…As it known, the dissolved oxygen is an important indicator of aquatic life and water quality. The variability of dissolved oxygen has noticeable effects on behavioral process in fish such as feeding, swimming and migration [29]. The dissolved oxygen concentrations reached critical levels, below KEPA standard, for all six stations, indicating heavy pollution, possibly due to Mishref pump station broke down in late 2009.…”
Section: E Principal Component Analysis (Pca)mentioning
confidence: 92%